Phosphorylation of Rabies Virus Nucleoprotein Regulates Viral RNA Transcription and Replication by Modulating Leader RNA Encapsidation - Yang, Jun (American Society for Microbiology, 1999)
One of the major structural differences between rabies virus and vesicular stomatitis virus (VSV) is that the nucleoprotein (N) is the major phosphoprotein and the nominal phosphoprotein (P) is less phosphorylated in rabies virus, whereas P is the major phosphoprotein and N is not phosphorylated in VSV. We investigated the function of phosphorylation of rabies virus N after dephosphorylation of N with alkaline phosphatase or after changing the phosphorylated serine at position 389 to alanine by site-directed mutagenesis. The unphosphorylated N, in comparison to the phosphorylated N, was studied for its abilities to encapsidate rabies virus leader RNA and to support transcription and replication of a rabies virus minigenome. We found that unphosphorylated N binds more strongly to leader RNA than the phosphorylated N; however, the rates of transcription and replication of the rabies virus minigenome were significantly lower with the unphosphorylated N than with the phosphorylated N. This indicates that the phosphorylation of rabies virus N plays an important role in the regulation of rabies virus transcription and replication, probably via modulation of leader RNA encapsidation.